An international dialogue about electric vehicle deployment to bring energy and greenhouse gas benefits through 2030 on a well-to-wheels basis. (September 2019) - Ehrenberger, Simone I.; Dunn, Jennifer B.; Jungmeier, Gerfried; Wang, Hewu
Highlights: Increased adoption of EVs is assessed on a well-to-wheel basis for five countries. EVs emit less greenhouse gases than gasoline-fueled vehicles in all countries. Complexity of EV analysis across boundaries complicates communication of benefits. Abstract: In this paper, we aim to assess the potential influence of increased adoption of electric vehicles (EVs) on a well-to-wheel (WTW) basis in the four countries with highest passenger car sales (Germany, the United States, China, and Japan), and Norway which represents a highly renewable energy market on greenhouse gas emissions. To characterize these emissions, we define critical parameters regarding fleet composition, activity, efficiency and fuel production in each country. Overall, with today's technology at a national average level, on a per km driven basis, battery electric vehicles emit fewer greenhouse gases than conventional vehicles in all countries. Though vehicle energy consumption is similar in all countries, electricity production energy efficiency and greenhouse gas emissions per kWh electricity vary considerably, with Norway and China representing the low and high emitting endpoints, respectively. As electricity generation decarbonizes, EVs have the potential to be lower greenhouse-gas emitting than gasoline vehicles in all countries considered. The complexity of EV analysis across international boundaries, time periods, and environmental media complicates communication of EV benefits to stakeholders. Analysts must continue to address and clearly communicate the influence of EV and electricity production technology advancement into the future on EV impacts on all environmental media (air, water, land).